The girl with the brown crayon - Paley, Vivian Gussin, 1929-2019 (Harvard University Press, 1997)
Once again Vivian Paley takes us into the inquiring minds and dramatic worlds of young children learning in the kindergarten classroom. As she enters her final year of teaching, Paley tells in this book a story of farewell and a story of self-discovery - through the thoughts and blossoming spirit of Reeny, a little girl with a fondness for the color brown and an astonishing sense of herself, "This brown girl that's dancing is me," Reeny announces as her crayoned figures